Proceedings of SPE/DOE Enhanced Oil Recovery Symposium 1990
DOI: 10.2523/20234-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 31 Minnelusa Polymer Floods With 24 Minnelusa Waterfloods

Abstract: 75083·3836. Telex, 730989 SPEDAL. group is applied to the same generic Minnelusa reservoir at a fixed injection References and figures at end of paper. 557 rate to yield oil production in time-rate format. Economics are run based on these two production functions.Results show the polymer flood is economic and recovers an additional 7.5% OOIP over the waterflood.The polymer plus equipment cost is less than $2.00 per incremental barrel of oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The Minnelusa experiments produced total recovery between 46 and 68% OOIP. The range of recovery values is not unreasonable given the heterogeneity of this reservoir rock (Hochanadel et al 1990). These values are similar to the range observed in field recovery values (discussed below).…”
Section: Laboratory Experiments -Two-phase Experiments -Tertiary Modesupporting
confidence: 81%
See 2 more Smart Citations
“…The Minnelusa experiments produced total recovery between 46 and 68% OOIP. The range of recovery values is not unreasonable given the heterogeneity of this reservoir rock (Hochanadel et al 1990). These values are similar to the range observed in field recovery values (discussed below).…”
Section: Laboratory Experiments -Two-phase Experiments -Tertiary Modesupporting
confidence: 81%
“…When there were multiple samples from a single well, preference was given to production over DST samples and the earliest (pre-waterflood) production sample over later production samples. Recovery factors were calculated for fields in which oil and water production, total pore volume and OOIP were reported (Towler and Griffith 1990, Hochanadel et al 1990, Mack and Duvall 1990.…”
Section: Description Of Equipment and Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present survey, we classified them as polymer floods because of (1) the large size of the anionic polymer banks compared with the other chemical banks, and (2) the approach taken during the design and reporting of these projects. 15,16 Gel Treatments in Injection Wells. The results of our survey of injection-well gel projects are summarized in Table 1.…”
Section: Literature Review Of Field Applicationsmentioning
confidence: 99%
“…The current study attempts to determine if similar results have been seen in the field by examining the projected recovery from 20 Minnelusa water-floods in the Powder River Basin. Hochanadel et al 15 have previously compared Minnelusa floods to determine the efffectiveness of polymer injection to increase the recovery. They found that polymer injection on average increased the oil recovery by 7.5% of OOIP.…”
Section: Introductionmentioning
confidence: 99%